2016
DOI: 10.1071/an15541
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-neutral wool farming in south-eastern Australia

Abstract: Ruminant livestock production generates higher levels of greenhouse gas emissions (GHGE) compared with other types of farming. Therefore, it is desirable to reduce or offset those emissions where possible. Although mitigation options exist that reduce ruminant GHGE through the use of feed management, flock structure or breeding management, these options only reduce the existing emissions by up to 30% whereas planting trees and subsequent carbon sequestration in trees and soil has the potential for livestock em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Studies have also shown the GHG emission benefits of land-use change from annual cropping to pastoral farming (140). Tree planting on farms can also make possible GHG-neutral livestock production (141). The key point here is the disconnect between the science that is informing climate action in the agricultural sector and the science that is informing the public health nutrition community about low-GHG-emission diets.…”
Section: Critical Review Of Metricsmentioning
confidence: 99%
“…Studies have also shown the GHG emission benefits of land-use change from annual cropping to pastoral farming (140). Tree planting on farms can also make possible GHG-neutral livestock production (141). The key point here is the disconnect between the science that is informing climate action in the agricultural sector and the science that is informing the public health nutrition community about low-GHG-emission diets.…”
Section: Critical Review Of Metricsmentioning
confidence: 99%
“…Well-managed livestock production systems can contribute to increasing agro and environmental land cover and biodiversity ( FAO, 2016 ). In addition, carbon-neutral and economically profitable livestock farming is achievable with the correct balance of trees, grassland, and livestock stocking density ( Doran-Browne et al, 2016 ). Other benefits of sustainable livestock farming include limiting soil erosion and water evaporation and providing habitats for a wide variety of invertebrate and vertebrate species ( Brandle et al, 2004 ).…”
Section: Ecosystem Services Contributionsmentioning
confidence: 99%
“…Agriculture can reduce or offset its greenhouse gas emissions through reforestation or agroforestry that sequester carbon dioxide (Doran-Browne et al 2016;Flugge & Abadi, 2006;Kragt et al 2012;Land & Water Australia, 2007). Articles 3.3 and 3.4 of the Australian ratified Kyoto Protocol allow for emission offsets through the sequestration of carbon.…”
Section: Reforestation As a Carbon Sinkmentioning
confidence: 99%